"Local" as an indicator of beef quality: An exploratory study of rural consumers in the southern U.S. (April 2017) - Telligman, Amy L.; Worosz, Michelle R.; Bratcher, Christy L.
Highlights: Consumer definitions of local beef and perceptions of beef quality are explored. Local beef was equated with having access to information about the producer, the farm, and the production practices. Consumers derived trust and assurances from both real and perceived relationships which reinforced quality inferences made about local beef. Quality inferences made were made about credence attributes. U.S. beef quality perceptions are discussed in relation to European studies about local foods and beef quality. Abstract: A 'turn' to quality is frequently associated with the proliferation of alternative agrifood networks and food system localization has been a prominent expression of such efforts. Yet quality is subjective and is influenced by historical, social, and cultural contexts. While there is a strong tradition of studying European consumers' quality perceptions, less is known about U.S. consumers. Due to increasing consumer interest in local beef, this paper examines U.S. consumer definitions of local beef and how these notions inform consumers' perceptions of beef quality. This study investigated beef consumers (N = 174) at grocery stores across Alabama using face-to-face intercept surveys designed to elicit meanings associated with the term 'local beef'. Content analysis identified five major definition types: geographic, production, knowledge, relational, and sociopolitical. Consumers' top-of-the mind definitions also provided insight into how and what type of quality inferences consumers made about local beef. Analysis revealed that local beef was perceived as quality cue that was generally tied to a specific geographic area (80.3%). Overall, quality inferences were made about local beef and shipping distances, freshness, type of animal feed, animal treatment, additives, and contributions to the local economy and community.